Role of titanium in bio implants and additive manufacturing: An overview. (2020) - Grover, Tarun; Pandey, Anamika; Kumari, Soni Tiwari; Awasthi, Ankita; Singh, Bharat; Dixit, Prashant; Singhal, Piyush; Saxena, Kuldeep K.
Abstract: For many years titanium-based biomedical devices are gaining a promising place in modern society. Titanium is one of the best suitable materials for manufacturing bio implants and its application areas are orthopedics, dentistry etc. There are many features possess by titanium which make it appropriate are its biocompatibility, resistance to corrosion, wearing, osteoporosis etc. The Cp- Titanium and titanium-based alloys are categorized in three ways depending upon its microstructure such as (α + β), α- type, β-type and comparative analysis are done its behavior, stability through SEM. This review paper discussed the conventional and modern methods of fabricating the bio-implants and also summarizes the various additive manufacturing techniques.